1971
DOI: 10.1172/jci106770
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of calcitonin and parathyroid extract in man

Abstract: A B S T R A C T To clarify the controversial renal action of calcitonin (CT) and a possible interrelationship between CT and parathyroid hormone, eight patients with untreated surgical hypoparathyroidism were studied. Various calcitonins, i.e. extracted porcine, synthetic porcine, synthetic human, and synthetic salmon CT in doses of 150 Medical Research Council U or 1.5 mg were infused over a 3 hr period. Subsequently, six of the same subjects received 500 USP U parathyroid extract (PTE) (Eli Lilly & Co., Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0
1

Year Published

1974
1974
1992
1992

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 32 publications
1
30
0
1
Order By: Relevance
“…Calcitonin lowers serum calcium levels through inhibition of bone resorption [37]. In the kidney, calcitonin stimulates the urinary excretion of calcium, phosphate, sodium, potassium and chloride, and enhances 1,25-dihydroxycholecalciferol production [5,20,25,32].…”
Section: Summary Calcitonin Gene-related Peptide (Cgrp)mentioning
confidence: 99%
See 2 more Smart Citations
“…Calcitonin lowers serum calcium levels through inhibition of bone resorption [37]. In the kidney, calcitonin stimulates the urinary excretion of calcium, phosphate, sodium, potassium and chloride, and enhances 1,25-dihydroxycholecalciferol production [5,20,25,32].…”
Section: Summary Calcitonin Gene-related Peptide (Cgrp)mentioning
confidence: 99%
“…Calcitonin exerts pronounced tubular effects such as the enhancement of the urinary fractional excretion of sodium, chloride, potassium, calcium and phosphate, and stimulation of urinary flow [5,20,32].…”
Section: Renotubular Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ECT in the dose used here appears to act directly on kidneys and reduce renal excretion of calcium. In contrast, calcitonin produces hypercalciuria in humans (15)(16)(17)(18) and sheep (19), possibly by its action on renal tubular reabsorption. The fact that the plasma calcium was lowered despite a decrease in calcium excretion suggests that ECT inter feres with bone resorption of calcium and may promote calcium bone deposition (20).…”
Section: Effect Of Ect On Renal Hemodynamicsmentioning
confidence: 99%
“…It is well known that calcitonin (CT) has a hypocalcemic effect which is reportedly attributed to the inhibition of bone resorption (Johnston et al, 1966), the reduction of intestinal calcium absorption (Olson et al, 1972), and the increase in urinary calcium excretion (Haas et al, 1971) by a hormone. Recently it was reported that the excretion of calcium into the bile is increased by the ,plevation of serum calcium, and that the increase in bile calcium excretion is prevented by thyroparathyroidectomy (Yamaguchi and Yamamoto, 1978a).…”
mentioning
confidence: 99%